Estudo comparativo dos métodos usados para medir a obsolescência da literatura científica - Barboza, Elza Maria Ferraz (1978)
Comparative study of the methods used to measure the obsolescence rate of scientific literature. There are two ways to approach the published scientific literature decay through the citation analysis: 1) to follow how the citations of a sample collected from published articles decline against time; 2) to chose a sample collected from current literature and observe how the cited sources within are scattered according to their publication date The research was done in the MEDICINE field (specially PULMONAR TUBERCULOSE), and the sources used to get the samples were: the Cumulated Index Medius (CIM) 1964, the Index Medicus (IM) 1975, and the Science Citation Index (SCI) 1964-75. The synchronous decay despite the fact of being more easier to be establishes presents difficulties in relation to the data survey. Its results show in general, a more accurate picture than the diachronous situation but gives an exaggerated rate of literature obsolescence The methods are compared and the results show that there are significant differences among them. They do not have the tendency to be similar. New studies must be done using large scale samples in other fields of human knowledge.